Temporary work, permanent strain? Personal resources as inhibitors of temporary agency workers’ burnout - Gomes, Sofia (2022)
Temporary workers already represent a relevant percentage of the total workforce in several European countries. This type of employment is usually associated with more precarious contractual and working conditions. This situation can lead to several negative outcomes in terms of workers’ physical and mental health. According to Job Demands-Resources (JD-R), the precarious situation of temporary workers can reduce the number of available resources and lead to mental health problems. This research aims to examine the importance of personal resources—in the form of resilience—with burnout and its three dimensions (emotional exhaustion, depersonalization, and personal fulfillment), as a consequence of the job strain generated by this employment. The empirical study follows a quantitative, correlational, and cross-sectional approach. A sample of 2050 individuals participated in the study. Responses were collected through an online questionnaire for Portuguese temporary workers in March 2021. The questionnaire was sent to active temporary workers registered in temporary agencies The hypotheses established through a structural model were tested by the Partial Least Square method. The results show that resilience, as a personal resource, is related to the three dimensions of burnout (emotional exhaustion, depersonalization, and personal fulfillment). As such, personal resources can be considered an important aspect to take into account when managing temporary agency workers’ burnout levels. Theoretically, this research contributes to understanding the role of personal resources, especially resilience as an important inhibitor of negative effects on workers’ mental health, such as burnout. Empirically, this study contributes to the discussion of the mental health challenges of temporary agency workers, reinforcing the importance of developing strategies to strengthen personal resources as a way to improve mental health.